2021
DOI: 10.1002/mde.3478
|View full text |Cite
|
Sign up to set email alerts
|

Corporate philanthropic giving and nature of stock market reaction: Evidence from China

Abstract: This study examines whether enterprises can obtain abnormal returns through philanthropic giving during public health emergencies, such as the COVID‐19 crisis, by using an event study approach to conduct an empirical analysis. The results show that if enterprises participate in philanthropic giving during the COVID‐19 crisis, they can obtain abnormal returns in the stock market. The extent of this market reaction is directly proportional to the level of philanthropic giving, and it is more significant for priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Using the event study method and the difference-in-difference method for regression analysis, it is concluded that H1, H2, and H3 all pass the test and, at the same time, pass the robustness test, indicating that the research results are robust and reliable. This paper finds that non-state-owned enterprises have higher social attention than state-owned enterprises in emergency donation and have better stock market performance, which is consistent with the conclusion of Zhu and Zhang (2021) . This paper also draws a new conclusion, in the construction of emergency projects, construction enterprises with engineering participation will obtain more social concern and, therefore, better stock market response.…”
Section: Empirical Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…Using the event study method and the difference-in-difference method for regression analysis, it is concluded that H1, H2, and H3 all pass the test and, at the same time, pass the robustness test, indicating that the research results are robust and reliable. This paper finds that non-state-owned enterprises have higher social attention than state-owned enterprises in emergency donation and have better stock market performance, which is consistent with the conclusion of Zhu and Zhang (2021) . This paper also draws a new conclusion, in the construction of emergency projects, construction enterprises with engineering participation will obtain more social concern and, therefore, better stock market response.…”
Section: Empirical Analysissupporting
confidence: 85%
“…The different natures of corporate equity will lead to different stock market reactions. Scholars Hoi, Zhang, and Zhuhave showed that the role of charitable donations in promoting corporate performance is more robust in non-state-owned enterprises than in state-owned enterprises (Zhang et al, 2016;Hoi et al, 2019;Zhu and Zhang, 2021). The main reason is that the public expects state-owned enterprises to fulfill their social responsibility more than non-state-owned enterprises.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…For example, Gao et al ( 2012 : 363) found a positive investor reaction to CPDR announcements in response to the 2008 Wenchuan earthquake in China, but only for Business-to-Consumer companies. Relatedly, Zhu and Zhang ( 2022 ) also found a positive investor reaction in China during the COVID-19 epidemic, but only for privately-owned enterprises. However, Muller and Kräussl ( 2011 ) found a negative yet insignificant shareholder reaction to U.S. firms’ CPDR after Hurricane Katrina in 2005.…”
Section: Research On Corporate Philanthropy and Natural Disasters: Th...mentioning
confidence: 98%
“…Gao et al ( 2012 : 368) suggested very briefly that this signaling effect might be one of the reasons along with the ‘buying goodwill’ effect for the positive shareholder reaction to CPDR they found, but they did not attempt to parse out the two effects. Zhu and Zhang ( 2022 ) explored briefly and found support for this explanation but did not ground their study in a broader conceptual framework to link back to theory.…”
Section: Research On Corporate Philanthropy and Natural Disasters: Th...mentioning
confidence: 99%
“…Second, we contribute to the literature on corporate philanthropy by examining the role of major customers. Extant research has examined the role of the government and social activists in the field (Gao & Yang, 2016;Luo et al, 2016;Zhu & Zhang, 2022). However, the role of major customers has largely been overlooked.…”
Section: Introductionmentioning
confidence: 99%